Different landscapes of the municipality of Ubatuba- SP: a geographic study - Melo, Kelly Cristina; Furlan, Sueli Ângelo (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2017)
In Geography, it is known that landscape study is of basic importance to un- derstand the phenomena that result of the relationship between social and envi- ronmental dynamics, allowing the relation between time/social space and time/ natural space to be evaluated. This work presented here is about identifying lan- dscape units in the city of Ubatuba-SP, considering the landscape analysis throu- gh the comprehension of the determining aspects of physical and social envi- ronment, and highlighting the importance of spatializing to build up a synthesis represented by environmental cartography. The landscape compartmentalizati of Ubatuba in units was based mainly on geomorphological, geological and vege- tative aspects, resulting in the identi cation of 12 units, representing the mosaic that composes that landscape.